2018
DOI: 10.1053/j.semnuclmed.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-Specific Bacterial Imaging in Nuclear Medicine

Abstract: When serious infections are suspected, patients are often treated empirically with broad-spectrum antibiotics while awaiting results that provide information on the bacterial class and species causing the infection, as well as drug susceptibilities. For deep-seated infections, these traditional diagnostic techniques often rely on tissue biopsies to obtain clinical samples which can be expensive, dangerous, and has the potential of sampling bias. Moreover, these procedures and results can take several days and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 158 publications
1
54
0
Order By: Relevance
“…From preclinical studies in vivo it has been shown that 99m Tc-UBI 29-41 (coordination unknown) and 99m Tc-HYNIC UBI 29-41 (Scheme 4) accumulated specifically in infected tissues with abscessto-muscle ratios between 2 and 3 [14,56,57]. Both recently developed PET analogues 68 Ga-NOTA-UBI 29-41 [12,[58][59][60][61] and 68 Ga-NOTA-UBI 31-38 [62] showed comparable uptake characteristics in infected thigh muscles in mice and rabbits. However, UBI 29-41 also accumulated in infections with the yeast C. albicans [63], which reduces specificity of this tracer for imaging of bacterial infections alone.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…From preclinical studies in vivo it has been shown that 99m Tc-UBI 29-41 (coordination unknown) and 99m Tc-HYNIC UBI 29-41 (Scheme 4) accumulated specifically in infected tissues with abscessto-muscle ratios between 2 and 3 [14,56,57]. Both recently developed PET analogues 68 Ga-NOTA-UBI 29-41 [12,[58][59][60][61] and 68 Ga-NOTA-UBI 31-38 [62] showed comparable uptake characteristics in infected thigh muscles in mice and rabbits. However, UBI 29-41 also accumulated in infections with the yeast C. albicans [63], which reduces specificity of this tracer for imaging of bacterial infections alone.…”
Section: Imaging Of Infections With Antimicrobial Peptidesmentioning
confidence: 99%
“…This review is an update of our earlier review published in 2013 [14], as well as other thematic reviews [12,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous efforts to develop pathogen-specific PET imaging methods have classically focused on radiolabeling existing antibiotics or antimicrobial peptides. 7 10 While this approach builds upon known chemistry and target interaction, both antibiotics and antimicrobial peptides are pharmacologically active and may paradoxically destroy the bacteria and interfere with the signal. Also, these compounds lack the capacity for signal amplification that could be achieved with agents that accumulate in bacteria.…”
mentioning
confidence: 99%
“…Given that current imaging techniques remain nonspecific for imaging bacterial infections, there remains a need for developing bacteria-specific radiotracers that identify a wide range of clinically relevant bacteria with high sensitivity. 1 After approximately 1000 small molecules were screened, several promising candidates were identified for radiolabeling and imaging infections, including paraaminobenzoic acid (4-aminobenzoic acid; PABA). In tritiated form, PABA was demonstrated to accumulate in a broad class of bacteria including Gram-positives, Gramnegatives (as well as Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%